Empowerment Of Siamese Citrus Farmers Kamang Nagari Kamang Hilir, Kamang Magek District, Agam Regency - Mutiara, Vonny Indah; Hariance, Rika (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2021)
Siam Kamang citrus farmers, who are known for their JESIKA products in Nagari Kamang Hilir, Kamang Magek District, Agam Regency, have been cultivating oranges since 1962. During its development, Siamese citrus farming experienced a period of production failure due to the CVPD virus attack. Excessive use of pesticides has affected the development of Siamese orange agribusiness in Nagari Kamang. Community service activities in the form of disseminating research results on prospects for developing Siamese orange agribusiness and the financial feasibility of Siamese citrus business are carried out in an effort to empower farmers to develop Siamese citrus farming. From the FGD activities carried out, farmers finally realized that farming patterns that use pesticides as an effort to prevent pests and diseases incur large costs and have a negative impact on the development of JESIKA agribusiness. Farmers are advised to cultivate JESIKA in accordance with the recommended SOP and apply a polyculture cropping pattern with an organic farming system to increase production more optimally